Art 2031 Strategies, Obstacles, and Perceptions of MSMEs in Bandar Masilam, Simalungun Regency in Implementing QRIS as a Digital Payment Tool - Intan Juwita Damanik; Rahmi Syahriza; Tuti Anggraini (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
This study aims to analyze the strategies, obstacles, and perceptions of MSME actors in Bandar Masilam District, Simalungun Regency in implementing QRIS as a digital payment tool. This research uses a qualitative method with a descriptive approach, with data collection techniques through interviews, observations, and documentation. The results show that QRIS implementation is still simple and passive, such as providing QR codes at business locations. The main obstacles include limited internet access, delays in fund disbursement, and low digital literacy among the comunity. However, MSME actors generally have positive perceptions. Therefore, improving digital literacy and infrastructure support is necessary to optimize QRIS adoption in the area